CONTRIBUTION OF THE HEART OF BORNEO (HoB) INITIATIVE TOWARDS BOTANICAL EXPLORATION IN SABAH, MALAYSIA - Sabran, Suzana; Nilus, Reuben; Pereira, Joan T.; Sugau, Joan Baptist; Kugan, Frederick (REINWARDTIA, 2014)
The Heart of Borneo (HoB) declaration is a conservation agreement initiated by WWF and signed by three countries, i.e., Brunei Darussalam, Indonesia and Malaysia in Bali, Indonesia on 12th February 2007 to protect more than 23 million hectares of forested region on Borneo Island. These forested areas could be well protected when conservation management plan is in place. One of the crucial activities to facilitate the planning and formulation of conservation plan is to conduct scientific expeditions that include botanical exploration. The primary objective of the expedition is to identify the key conservation targets within the forest reserves. For the past five years, several expeditions have been conducted by the Sabah Forestry Department under the auspices of the HoB project to explore various forest reserves with conservation issues within the Heart of Borneo area. This paper will present the findings which include plant richness, endemism and plant conservation status in each forest reserves that has been explored.